Identification of active gully erosion sites on the loess plateau based on terrain profile lines - Shan He; Jilong Li; Han Wu; Tianjiao Cui (International Journal of Digital Earth, 2025)
Accurately identifying active gully erosion sites across a small-scale region under typical catchment conditions is essential for effectively managing and mitigating soil erosion on the Loess Plateau. This paper presents a comprehensive methodology integrating high-accuracy digital elevation model (DEM) data with 23 Sentinel-1A data. We first generated gully topographic profiles in the Zhifang Catchment (Ansai District) through DEM processing using the multiple-flow-direction (MFD) algorithm. Subsequently, active erosion sites were detected through ensemble empirical mode decomposition (EEMD) combined with Hilbert-Huang Transform (HHT) spectral analysis. Finally, using Small Baseline Subset-Interferometric Synthetic Aperture Radar (SBAS-InSAR) technology, to characterize the topographic variation in the study area and verified the identification results. Analysis of 8 representative topographic profiles revealed 12 active erosion sites exhibiting deformation rates ranging from −29.1 to 29.2 mm/a. The overall accuracy of the identified active erosion sites was 75%, with notable concentration of active erosion features at gully heads. This study further analyzed typical active gully erosion sites on the Loess Plateau, providing a reference for monitoring and identifying gully erosion in small-scale catchments of the Loess Plateau.